Hymenoptera Allergens: From Venom to “Venome” - Spillner, Edzard; Blank, Simon; Jakob, Thilo (Frontiers in Immunology, 2014)
In Western Europe hymenoptera venom allergy primarily relates to venoms of the honeybee and the common yellow jacket. In contrast to other allergen sources, only a few major components of hymenoptera venoms had been characterized until recently. Improved expression systems and proteomic detection strategies have allowed the identification and characterization of a wide range of additional allergens. The field of hymenoptera venom allergy research has moved rapidly from focusing on venom extract and single major allergens to a molecular understanding of the entire “venome” as a system of unique and characteristic components. An increasing number of such components has been identified, characterized regarding function and assessed for allergenic potential. Moreover, advanced expression strategies for recombinant production of venom allergens allow selective modification of molecules and provide insight into different types of IgE reactivities and sensitization patterns. The obtained information contributes to an increased diagnostic precision in hymenoptera venom allergy and may serve for monitoring, reevaluation and improvement of current therapeutic strategies.